Clinical and molecular characterisation of hereditary dopamine transporter deficiency syndrome: an observational cohort and experimental study - Kurian, Manju A.; Li, Yan; Zhen, Juan; Meyer, Esther; Hai, Nebula; Christen, Hans-Jürgen; Hoffmann, Georg F.; Jardine, Philip; von Moers, Arpad; Mordekar, Santosh R; O'Callaghan, Finbar; Wassmer, Evangeline; et al. (The lancet, 2011)
Background - Dopamine transporter deficiency syndrome is the first identified parkinsonian disorder caused by genetic alterations of the dopamine transporter. We describe a cohort of children with mutations in the gene encoding the dopamine transporter (SLC6A3) with the aim to improve clinical and molecular characterisation, reduce diagnostic delay and misdiagnosis, and provide insights into the pathophysiological mechanisms. - Methods - 11 children with a biochemical profile suggestive of dopamine transporter deficiency syndrome were enrolled from seven paediatric neurology centres in the UK, Germany, and the USA from February, 2009, and studied until June, 2010. The syndrome was characterised by detailed clinical phenotyping, biochemical and neuroradiological studies, and SLC6A3 mutation analysis. Mutant constructs of human dopamine transporter were used for in-vitro functional analysis of dopamine uptake and cocaine-analogue binding. - Findings - Children presented in infancy (median age 2·5 months, range 0·5-7) with either hyperkinesia (n=5), parkinsonism (n=4), or a mixed hyperkinetic and hypokinetic movement disorder (n=2). Seven children had been initially misdiagnosed with cerebral palsy. During childhood, patients developed severe parkinsonism-dystonia associated with an eye movement disorder and pyramidal tract features. All children had raised ratios of homovanillic acid to 5-hydroxyindoleacetic acid in cerebrospinal fluid, of range 5·0-13·2 (normal range 1·3-4·0). Homozygous or compound heterozygous SLC6A3 mutations were detected in all cases. Loss of function in all missense variants was recorded from in-vitro functional studies, and was supported by the findings of single photon emission CT DaTSCAN imaging in one patient, which showed complete loss of dopamine transporter activity in the basal nuclei. - Interpretation - Dopamine transporter deficiency syndrome is a newly recognised, autosomal recessive disorder related to impaired dopamine transporter function. Careful characterisation of patients with this disorder should provide novel insights into the complex role of dopamine homoeostasis in human disease, and understanding of the pathophysiology could help to drive drug development. - Funding - Birmingham Children's Hospital Research Foundation, Birth Defects Foundation Newlife, Action Medical Research, US National Institutes of Health, Wellchild, and the Wellcome Trust.
Available online 25 November 2010
Gesehen am 11.07.2022